Ideological conflict and the rule of law in contemporary China : useful paradoxes / Samuli Seppänen. - Seppänen, Samuli (Law in context., 2016)
This book is an informative and thought provoking study in understanding the ideological divisions within Chinese legal academia and their relationship to arguments about the rule of law. It describes argumentative strategies used by Chinese legal scholars to legitimize and subvert China's state-sanctioned ideology and examines Chinese efforts to invent new, alternative rule of law conceptions. In addition to this descriptive project, the book advances a more general argument about the rule of law phenomenon, insisting that many arguments about the rule of law are better understood in terms of their intended and actual effects rather than as logical propositions or other good faith arguments. To illustrate this proposition, the book demonstrates that various paradoxical, contradictory and otherwise implausible arguments about the rule of law play an important role in the Chinese debates. More specifically, paradoxical statements about the rule of law can be 'useful' for an ideological project.